MODALITY REALIZED ON HORTATORY EXPOSITION TEXTS USED IN SENIOR HIGH SCHOOL GRADE XI TEXTBOOK - Hani Suciati; Bambang Ruby Sugiarto (Journal of English Education Program (JEEP), 2021)
This research is aimed at analyzing types of modality and the interpersonal meaning through modality system realized in hortatory exposition texts that is used by senior high school grade XI textbook. This study employed Systemic Functional Grammar (SFG) based on Halliday and and Matthiessen’s framework since it can seek and identify the level of language structure which makes kinds of meaning. There are five hortatory exposition texts that were analyzed based on modality system and interpersonal meaning. The first finding showed that there was modality system in all of clauses indicating  author’s interpersonal meaning with the use of language value that is different in the texts. The second finding showed that different types of language value and polarity also indicated the author’s interpersonal meaning in the texts. The types of modality which were found in the five texts were dominated by modalization with positive polarity and median value. In addition, this analysis concluded that five texts comprised several modalization and modulation types which occurred in different ranks. This study suggested that further researchers investigate various texts and other aspects of mood and modality. Keywords: hortatory exposition text, interpersonal meaning, modality, textbook